The economic implications of introducing carbon taxes in South Africa - Theresa Alton; Channing Arndt; Rob Davies; Faaiqa Hartley; Konstantin Makrelov; James Thurlow; Dumebi Ubogu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
South Africa is considering introducing carbon taxes to reduce greenhouse gas emissions. We evaluate potential impacts using a dynamic economy-wide model linked to an energy sector model. Simulation results indicate that a phased-in carbon tax that reaches US30 per ton of CO2 by 2022 achieves the ambitious national emissions reductions targets set for 2025. Relative to a baseline with free disposal of CO2, constant world prices and no change in trading partner behaviour, the preferred tax scenario reduces national absorption and employment by 1.2 and 0.6 per cent, respectively, by 2025. However, if South Africa's trading partners unilaterally impose a carbon consumption tax then welfare and employment losses exceed those of a domestic carbon tax. Border tax adjustments improve welfare and employment while maintaining the same emissions reductions. The mode for recycling carbon tax revenues strongly influences distributional outcomes, with tradeoffs between growth and equity.
Keywords: D58; H23; O13; O44; 330; carbon tax; growth; employment; income distribution; South Africa; Ökosteuer; Wirtschaftswachstum; Beschäftigungseffekt; Einkommensverteilung; Südafrika